BURUH PEREMPUAN DI TENGAH KUBANGAN PARA KORUPTOR - Sofiani, Triana (IAIN Pekalongan, 2012)
Abstract : The Center of hegemony, which is built on the common values common interests between the rulers and capitalists who incidentally are in the sex of